USE OF GIS AND MICROHABITAT PREDICTORS FOR POSSIBLE SITE OCCUPANCY OF THE HEIDELBERG OPAL BUTTERFLY (CHRYSORITIS AUREUS) W ITHIN GAUTENG PROVINCE, SOUTH AFRICA - N.P. Faria; M.D. Panagos; W.J. Myburgh; R. Deysel (Journal of Animal and Plant Sciences, 2019)
The Heidelberg Opal butterfly (Chrysoritis aureus) is currently classified as endangered with a total of nine known localities in Gauteng. Recent work on the fine scale habitat requirements of C. aureus provided the opportunity to expand the search for additional suitable habitats for this species in the Gauteng Province, using GIS and current distribution databases. A topographical base map and overlays of food plant (Clutia pulchella), host cocktail ant (Crematogaster liengmei) distributions and geology (Ventersdorp Supergroup) were used to determine possible additional sites suitable for C. aureus. Eight potentially suitable sites were identified. Four of these sites where transformed by mining activities and thus excluded. One of the four remaining sites was deemed suitable for C. aureus as both the food plant (C. pulchella) and the host ant (C. liengmei) were present. C. aureus was not recorded at any of the other sites surveyed probably due to season of site visits (winter).
Keywords: Chrysoritis aureus; habitat; Clutia pulchella; Crematogaster liengmei